Integrating IoT Devices with Distribution Energy Management System by Harmonizing Their Logical Models Using IEC Standards 61970/61968 and 61850 - Leite, Jonatas Boas [UNESP]; Kezunovic, Mladen (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In the information era, microprocessor-based devices are being incorporated into human environment facilitating the human-machine relationship. Recently released credit card-sized computers are being used in internet of things (IoT) platforms originated from ubiquitous computing concepts. In the modern power system, ubiquitous computing systems can be configured to facilitate the transfer of energy by supporting various smart grid applications at the grid edge. Using such distributed computational resources is not trivial considering that the traditional power system energy management technology is mostly centralized. The use of the IoT technology requires interfacing of the distributed computational resources with the legacy centralized resources where microprocessor-based IoT nodes are interfaced to the advanced distribution management system and perform the distribution automation functions. This paper demonstrates how such devices are modeled by harmonizing IEC 61970/61968 and 61850 standards over a multi-tier computational model. The performed tests analyze the message flow of the fully automated procedures for fault location, isolation and service restoration applications.
Keywords: Advanced Distribution Management System; Distribution Network Operation; Internet of Things; Microprocessor-based IoT node